Case Report: Postmortem brain and heart pathology unveiling the pathogenesis of coexisting acute ischemic stroke and electrocardiographic abnormality - Hattori, Yorito; Ikeda, Shuhei; Matsumoto, Manabu; Tagawa, Naoki; Hatakeyama, Kinta; Ihara, Masafumi (Frontiers in Cardiovascular Medicine, 2023)
Electrocardiography abnormalities have been occasionally reported at the onset of stroke. Simultaneous electrocardiographic abnormalities and stroke require a rapid differentiated diagnosis among several diseases. However, direct causal relationships remain unclear. A 92-year-old woman presented to our emergency department in a sudden-onset coma. The patient suffered from huge acute ischemic stroke with bilateral internal carotid artery occlusion assessed by brain magnetic resonance imaging, and her electrocardiography showed ST-segment elevation at II, III, aVF and V4–6, and atrial fibrillation (AF). However, the etiology of the medical condition was clinically unknown. Eventually, the patient died on day 4 of hospitalization before the diagnosis could be completed. Therefore, an autopsy was performed to investigate pathological findings after obtaining informed consent from the family. A postmortem pathological evaluation demonstrated that fibrin mural thrombi in the left atrial appendage (LAA), and the cerebral and coronary arteries possessed CD31-positive endothelial cells, and CD68-positive and CD168-positive macrophages in a similar fashion, suggesting the fibrin thrombi observed in the three sites implicated to be identical. We concluded that nearly concurrent cerebral and coronary artery embolism because of the fibrin thrombi in LAA developed by AF. Simultaneous cerebral infarction and myocardial infarction are referred to as cardiocerebral infarction (CCI), a rare disorder for which clear pathomechanisms remain unknown, although several mechanisms of CCI have been proposed. We first revealed the clear pathology of CCI using the autopsy. Additional pathological studies are warranted to establish clear pathomechanisms and preventive strategies of CCI.